THE MEXICAN FOOD INDUSTRY INVESTMENTS Situation and Opportunities in the Czech Republic - Moctezuma Figueroa, Abihu Antonio; Gutiérrez Chvalkovská, Jana; Inostroza Pino, Luis; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2013)
This thesis aims to analyze the evolution of the investments of Mexico in foreign countries, its beginnings, the economic policy behind the boost on investments, the main Mexican industries evolution of investments in the globe and the specific food industry development through the years. To reach the final analysis of the specific opportunities of three of the biggest companies in the Mexican food sector, Grupo BIMBO, Grupo MASECA and Conservas La Costena, which will have conclusions on the Czech conditions for businesses, competition in the food industry by domestic companies and the description of the capacities of each Mexican enterprise that may or may not enable them to invest in the Czech Republic. The first chapter analyzes a theoretical approach to the global context dynamics and the theories that we believe are proper for the investment flows analysis along with the performance of Mexico in this dynamics. The second chapter covers the development of the outward Mexican FDI linked to some historical facts, policies and reaching an analysis on the evolution of Mexican FDI presence in Europe. The Chapter three deepens the study in the food sector, with a global contextualization of the dynamics in and out of Mexico, and then analyzes our three specific cases, BIMBO, GRUMA and LA COSTENA. Finally, the fourth chapter will end with the analysis of the Czech Republic as a potential investment receiver, barriers, legal framework, and competition in the food sector, to reach the final description and conclusions about the opportunities of Mexican investments in the food sector on the Czech Republic.
Vedoucí práce: Jana Gutiérrez Chvalkovská
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2013
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2013
Způsob přístupu: Internet
Keywords: ekonomická a regionální studia latinské ameriky [obor dipl. práce]; diplomové práce; master's theses